Asociation between fluid overload and mortality in pediatric patients in the intensive care unit - Chávez-Valdivia, Alexi (2022)
Objective: To assess the association between fluid overload (FO) and other risk factors in the mortality of patients admitted to the Pediatric Intensive Care Unit (PICU). Patients and Method: A historical cohort study was conducted. Pediatric patients older than one month and younger than 18 years who were hospitalized in the PICU for more than 48 hours during 2016 were included. Demographic and clinical data were recorded. FO was calculated as [Sum of daily (fluid in − fluid out)/weight at ICU admission] × 100. Poisson regression analysis was performed to determine factors associated with mortality. Results: 171 patients were included. The median age was 31 months (RIQ 8; 84). Mortality was 8.18%. FO in the surviving population was 7% and 11.5% in the deceased patients (p < 0.05). The adjusted analysis identified FO as a major risk factor for mortality with a Relative Risk 1.32 (1.24-1.40); age and Glasgow Coma Scale were protective factors. Conclusion: Fluid overload is an independent risk factor for mortality in the analyzed PICU cohort.